MPPT using modified salp swarm algorithm for multiple bidirectional PV-Ćuk converter system under partial shading and module mismatching. (October 2020) - Mao, Mingxuan; Zhang, Li; Yang, Lei; Chong, Benjamin; Huang, Han; Zhou, Lin
Highlights: A novel DWSSA-MPPT controller for each PV-Ćuk converter is proposed. Multiple bidirectional PV-Ćuk converter system model is presented. A state space model is developed for the PVCC and experimentally validated. The control strategy for a PV system having more than one PVCC is discussed. A simulated PV generator comprising three PV panels and two converters is verified. Abstract: This paper presents a configuration scheme based multiple bidirectional Ćuk converter with a modified salp swarm algorithm (SSA) based maximum power point tracking (MPPT) for photovoltaic (PV) system under partial shading and module mismatching. The proposed scheme is made up of multiple bidirectional PV-Ćuk converter (PVCC) modules in a series chain, a novel SSA with dynamic nonlinear w factor (DWSSA) based the distributed maximum power point tracking (MPPT) and a terminal step-up converter for load connection. First of all, the configuration offers the advantage that the PVCC provides a current by pass and can also be controlled to allow two PV panels in the module to track their available maximum power under partial shading or module mismatching. In addition, the DWSSA-MPPT control scheme is used to estimate the voltages corresponding to the maximum power each PV panel can generate under its specific weather conditions. Moreover, a state space model is developed for the PVCC and experimentally validated, and the control strategy for a PV system having more than one PVCC is discussed. Finally, a simulated PV system based the proposed configuration scheme is set up and results are analyzed, which demonstrates that compared with some existing algorithms, the scheme with DWSSA-MPPT method can highly be effective under partial shading and module mismatching.